2016
DOI: 10.21763/tjfmpc.271330
|View full text |Cite
|
Sign up to set email alerts
|

Management of Sarcopenia in Elderlies

Abstract: Improvement in living conditions, science and technology has enabled the management of several diseases. However, in elderly people new medical condition, which cannot be explained by other definitions of disease are evolving. These are called geriatric syndromes. Sarcopenia might be one of these syndromes. Commonly it is defined as loss of muscle mass and functionality due to aging. Changes of the body composition, significant decline of the muscle mass and functions due to aging leads to decrease of physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
(50 reference statements)
1
2
0
Order By: Relevance
“…[38][39][40] Most of these findings are also seen in elderly patients with sarcopenia. 2,23,35 Similar to the literature, in our study, the height, weight, BMI, muscle and visceral values were significantly lower in the sarcopenia group compared to the non-sarcopenia group in BD. However, it was found that waist circumference, right Upper-middle arm circumference (UMAC) and left UMAC values were higher in the sarcopenia group compared to the non-sarcopenia group.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…[38][39][40] Most of these findings are also seen in elderly patients with sarcopenia. 2,23,35 Similar to the literature, in our study, the height, weight, BMI, muscle and visceral values were significantly lower in the sarcopenia group compared to the non-sarcopenia group in BD. However, it was found that waist circumference, right Upper-middle arm circumference (UMAC) and left UMAC values were higher in the sarcopenia group compared to the non-sarcopenia group.…”
Section: Discussionsupporting
confidence: 89%
“…1 It may develop due to conditions such as inactivity, malnutrition and cachexia in young individuals. 2 European Working Group on Sarcopenia in Older People (EWGSOP) described sarcopenia as a syndrome qualified by a generalized and progressive loss of skeletal muscle mass and strength at risk of reverse outcomes like a poor quality of life, physical disability and death. 3 The incidence of sarcopenia increases with age.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing elderly population brings with it increasing health expenditures, the need for infrastructure regulation and problems. The adaptation process to the increasing elderly population is challenging, especially for economically underdeveloped and developing countries, and it is of great importance to identify the problems correctly and produce solutions quickly and feasibly [3].…”
mentioning
confidence: 99%